Butyrate-induced changes in nuclease sensitivity of chromatin cannot be correlated with transcriptional activation. - Birren, B W (1987)
We examined in the H4IIE rat hepatoma cell line the relationship between butyrate-induced changes in the nuclease sensitivity of chromatin and changes in transcriptional activity of specific genes. The butyrate-inducible metallothionein I (MT-I) gene underwent a dramatic increase in DNase I sensitivity after 3 h of butyrate treatment. However, genes not transcribed in H4IIE cells underwent the same changes in DNase I sensitivity. Thus, butyrate-induced increases in DNase I sensitivity are not sufficient for the transcriptional activation of a gene. Butyrate treatment has also been reported to alter the sensitivity of sequences to micrococcal nuclease (MNase) in a manner reflecting their tissue-specific expression. Butyrate exposure caused increased digestion of the MT-I gene by MNase. However, butyrate-induced MNase sensitivity also occurred for genes which are neither transcribed in untreated cells nor butyrate inducible. Moreover, cadmium, a potent transcriptional activator of the MT-I gene, does not alter the sensitivity of the MT-I gene to MNase. Thus, the butyrate-induced alterations in MNase sensitivity are neither sufficient for, necessary for, nor indicative of transcriptional activation.